ILMU PENOLOGI MODERN SEBAGAI ALAT BUKTI ZINA DALAM HUKUM PIDANA ISLAM (SEBUAH TINJAUAN TERHADAP PEMIKIRAN ABDULLAH AHMED AL-NAIM) - Syahrial, Muhammad (LEGALITE, 2016)
Proof of adultery in Islamic criminal law still apply the evidences formulated by jumhur classical law expert that is recognition, The witness must be four men who are all male and pregnancy guidance, but this evidence can not serve as the primary evidence but as a supporting evidence against the evidence of confession and testimony. While international human rights agreed by various countries in the world there is no discrimination against witnesses, as long as the witness is competent to be a witness. Furthermore on the application of the rules of modern penology on the proof of adultery, Is very necessary because the sciences are very supportive to prove to the defendant guilty or not. The modern penology sciences required for the prevention of adultery today are expert witnesses, letters under oath, electronic media, DNA tests, Visum et Repertum namely information from doctors taken under oath and observation / judge decision. Keyword: Ilmu Penologi Modern, Alat Bukti Zina, Hukum Pidana Islam